SOLUTIONS TO IMPROVE THE TRANSPORT PROCESSES OF TEMPORARY IMPORT- RE-EXPORT OF GOODS BY ROAD BETWEEN VIETNAM AND CAMBODIA - Dinh , Dang Quang; Phuong , Nguyen Hoang (International Journal of Psychosocial Rehabilitation, 2020)
Currently, transporting temporary import-re-export commodities of Vietnamese and Cambodian companies through those Southern Seaports of Vietnam are implemented by Vietnamese transportation companies. Those logistics services go along with transportation services are rather various and developing. However, in fact, there are some shortcomings and difficulties raised recently. This study is aimed evaluating current situation to find the advantages and difficulties of delivery processes to propose solutions to orient and develop delivery services of Vietnam to type of temporary import-reexport goods between Vietnam and Cambodia.